Intestinal Transport of Monosaccharides - Srichamroen, Anchalee (Asian Health, Science and Technology Reports, 2007)
Sugars are transported from the small intestinal lumen to blood circulation by transcellular or paracellular routes. The transcellular process needs protein transporters to mediate monosaccharide to cross lipid cell membranes. The facilitated-diffusion glucose transporter 5 (GLUT 5) facilitates fructose entering the enterocytes. Na+-dependent glucose transporter 1 (SGLT 1) actively transport glucose and galactose across the epithelial cell layers by sodium gradient within the enterocytes. This mechanism is maintained by the Na+-K+ ATPase enzyme located at basolateral membrane (BLM). All sugars exit from the enterocyte to blood circulation by facilitation of GLUT 2 at BLM. Regulation of the paracellular transport of glucose involves the tight junction permeability.